Peningkatan Literasi Digital Bagi Siswa Kelas XII SMA Jaya Kota Langsa - Puspita, Esti Alemia; Erniwiriani (Yayasan Pendidikan Mitra Mandiri Aceh(YPMMA), 2023)
Increasing digital literacy among class XII students of SMA Jaya, Langsa City, is the main focus in this community service. Digital literacy is an important ability in facing challenges and opportunities in today's digital era. Approach to the method of activities carried out in this community service. The proposed activity methods include digital literacy training, discussion sessions, drill methods. Through the training, students will acquire deep digital literacy understanding and skills. The discussion sessions encourage students to think critically and gain a broader understanding of digital literacy issues. The drill method helps students improve their understanding and mastery of digital literacy through intensive and repetitive practice. This community service activity aims to increase the digital literacy of class XII students at SMA Jaya Langsa City so that they can participate effectively in an increasingly complex digital world. In collaboration with educators, digital literacy experts, and students, it is expected to have a significant positive impact on students in understanding and managing technology wisely. With increasing digital literacy among Jaya High School students in Langsa City, it is hoped that they will become a generation that is ready to face challenges and opportunities in the digital world. It is important for stakeholders to work together in carrying out this activity in order to achieve maximum results and provide real benefits for students